(untitled) (Indonesian Journal of Agrarian Law, 2026)
Land acquisition for development for the public interest is an important instrument in supporting national development, but in practice it often raises legal disputes, especially regarding land ownership status, compensation, and legal certainty for affected parties. This study aims to analyze the legal considerations of judges in deciding land acquisition disputes in the public interest and examine the role of local governments and the National Land Agency in ensuring legal certainty, with a study on Decision Number 43/Pdt.G/2024/PN.Smg related to the construction of the Semarang-Demak Toll Road. The research method used is normative-empirical legal research with a descriptive-analytical approach. The normative approach is carried out through analysis of laws and regulations and court decisions, while the empirical approach is conducted through interviews and review of relevant documents. The results show that disputes are not solely caused by overlapping land ownership, but also by weak land administration and non-optimal recording of transfer of rights, causing uncertainty regarding parties entitled to compensation. The judge’s consideration in this case focused more on formal aspects and legal position of the parties, so the lawsuit was declared unacceptable. This research contributes to strengthening understanding of the importance of orderly land administration and inter-agency coordination in land acquisition. The conclusion emphasizes that the role of local governments and the National Land Agency determines the realization of legal certainty. Therefore, strengthening land administration management after land acquisition is necessary to prevent similar disputes in the future.